A novel ready-to-use loop-mediated isothermal amplification (LAMP) method for detection of Burkholderia mallei and B. pseudomallei - Mitsuru Nakase; Jeewan Thapa; Vanaabaatar Batbaatar; Ochirbat Khurtsbaatar; Batchuluun Enkhtuul; Jugderkhorloo Unenbat; Baasansuren Lkham; Sachiho Fujita; Ai Koshikawa; Apichai Tuanyok; Vannarat Saechan; Hideaki Higashi; et al. (BMC Microbiology)
Abstract Background Glanders and melioidosis are contagious zoonotic diseases caused by Burkholderia mallei and B. pseudomallei, respectively. Bacterial isolation and polymerase chain reaction (PCR) have been used to detect these bacteria in animals suspected of infection; however, both methods require skilled experimental techniques and expensive equipment. These obstacles make it difficult to diagnose B. mallei and B. pseudomallei infections in areas where reagents and equipment are difficult to procure. To solve this problem, we developed an easy and ready-to-use dried-format diagnostic tool based on loop-mediated isothermal amplification (LAMP) method. Results The primer set targeting the internal transcribed spacer (ITS) region detected 10 genomic copies of B. mallei DNA and B. pseudomallei DNA using the conventional liquid LAMP method. This primer set did not detect any other Burkholderia species. Using this novel primer set, a dried-format in-house LAMP method with high sensitivity and specificity was developed. This method was used to test for the presence of B. mallei DNA in swabs collected from the nasal cavity and ulcerated skin of 19 B. mallei-infected horses and five uninfected horses and was compared with the real-time PCR method. These two tests showed 87.5% agreement for the positive samples and 100% agreement for the negative samples. This method detected all tested B. pseudomallei clinical isolates. Conclusions We established the first dry LAMP method for the detection of B. mallei and B. pseudomallei. This study provided a simple, rapid, cost-effective, and sensitive diagnostic tool for glanders and melioidosis.